Technology and the Civil War - Mountjoy, Shane, 1967- (The Civil War : a nation divided, 2009)
During the Civil War, both sides experimented with developing technologies. Exploding shells, hot air balloons, anesthesia, land mines, submarines, and the telegraph are a few of the unique technologies that Union and Confederate leaders used in their struggle to win the war.